박은식과 정인보의 자아와 주체관 연구 - 진아(眞我)론과 실심(實心)론의 철학적 성격을 중심으로 - 김우형; Kim Woo Hyung (Yulgok sasang yŏn'gu, 2022)
본고는 박은식과 정인보의 주체와 자아에 관한 견해로서 진아(眞我)론과 실심(實心)론의 철학적 성격에 대해 상호 연관성에 초점을 맞춰 살펴보았다. 그들은 한국 근대양명학의 대표자로 널리 알려져 있지만, 여기서는 그들의 진아론과 실심론을 양명학의 맥락에 국한시키기 보다는, 근현대 한국철학의 형성에 관련시켜서 조명해보고자 하였다. 그들의 자아관과 주체관은 민족적 정체성의 확인과 자국 철학전통의 정립이라는 당시 동아시아의 사상적 흐름 속에서 형성된 것이었다. 진아와 실심은 과학적 철학적 인식의 주체이자 실천적 도덕수양의 주체로서의 성격을 띤다. 과학적 철학적 원리에 대한 탐구와 인식[지각]을 강조하는 점은 진아론과 실심론의 주요 특징이다. 이는 그들의 도덕론에 영향을 미치는데, 두 마음의 윤리적 갈등상태가 상정되고 의(意)에 자율성이 부여됨으로써 주체는 자유의지를 지니게 된다. 또한 진아와 실심은 존재론적인 실체는 아니지만, 시비를 직관하고 우주의 근본 원리를 자각하는 양지(良知)의 작용에 의해 영원성을 얻을 수 있다. 세부적인 차이에도 불구하고, 진아론과 실심론은 공통적으로 양명학의 방법을 통해 조선유학을 비판하되 독창적인 ‘한국철학’으로 전화(轉化)시켰다고 할 수 있다. This article examines the philosophy of Park Eun-sik and Jeong In-bo, focusing on their theories of jin-ah 眞我 (true self) and sil-shim 實心 (real mind) as their conceptions of the self and subjectivity. Their views on the self and subjectivity were formed in the flow and movement establishing national identity in East Asia at that time. Jin-ah and sil-shim have some characteristics as an agent in scientific research and moral cultivation. They thought that the methodology of science and moral cultivation need to be set differently, although the self to perform the jobs in the two areas is one. However, they commonly put stress on the research and cognition of scientific and philosophical principles. In moral cultivation, jin-ah and sil-shim have the implication of free will by assuming the conflict between two minds and by giving autonomy to ui 意 (volition). Meanwhile, jin-ah and sil-shim are also respectively identified with hon 魂 (spirit) and eol 얼 (pure Korean word corresponding to hon) as the entity of mind. The mind can enter the eternality mainly by the function of liangzhi 良知 (innate knowing) that is able to intuit the right and wrong and realize the fundamental cosmological principle. Despite the detailed differences, it can be evaluated that jin-ah theory and sil-shim theory transformed the traditional thought of Joseon Confucianism into “Korean philosophy” through Yangming learning.